Kulim airport to boost Kedah economy - The Edge, Financial Daily (The Edge Financial Daily, 2015)
The Kedah menteri besar said the whole area between the Kulim High Technology Park and the KXP would become a manufacturing and service industry development zone, building on the opportunity from the access to the outside world created by the KXP